The Influence of Endorphine Massage on Anxiety in Mothers During Their 3rd Trimester Pregnancy - Niken Sukesi (Humanistic Network for Science and Technology (HNST), 2020)
The 3rd trimester of pregnancy is the time for one to prepare both physiologically and psychologically for baby birth and nursing. The pregnancy during this final trimester causes incovenience due to fetus and uterus enlargements. The pain during pregnancy and approaching the labor in pregnant mothers might increase their anxiety. One of attempts to reduce this anxiety resulting from pain in pregnant mothers employs nonpharmacologic method in the form of endorphin massage. This research was quasi experimental with one group pretest posttest design. It used analytical comparative research method since the researcher tried to study the existence of endorphin massage influence on anxiety in pregnant mothers. The results revealed that there was some mean differences before and after the therapy was given. The mean score before the therapy was given was 1.6 and after the therapy was given was 1.2. The difference between these two mean score was 0.4. From the analysis, it was found that the p-value was 0.037, meaning that there was a significant difference of anxiety level between before and after the provision of endorphin massage. Keywords: endorphin; pregnancy; anxiety